Ungkapan Tabu dalam Sapaan Kekerabatan Bahasa Galela pada Masyarakat Desa Duma Kecamatan Galela Barat - Boriri, Agus; Djais, Idwan; Bane, Katriani; Tawakali, Fadila (Fakultas Ilmu Budaya, Universitas Jambi, 2022)
This research aims to identify and describe taboo expressions in kinship greetings in the Galela language in order to provide understanding to the Duma Village community, West Galela District, regarding the use of kinship greetings correctly in order to maintain the norms of kinship greetings in the Galela language. This study uses qualitative methods by relying on content analysis techniques. In collecting data using direct participatory observation method in Duma Village, West Galela District. Taboo expressions in kinship greetings in the Galela language found two taboos, namely greeting taboos based on politeness norms that are used as life guidelines in interacting with others, especially in kinship relations, namely greetings baba, baba ria, dodo, meme ria, oa, ria, bira, nongru, ete, topora, memes ma awa, dunu, tunu, awa ma awa, awa ma baba, hodo/moli, toroa, tiopo, tapu, dapu, and doroa/mod'oka. The greeting taboo based on mystical norms is always related to supernatural powers. The people of Duma Village, West Galela District believe that the taboo of kinship greetings in the Galela language contains a mystical power known as giki i tapano (reprimand of ancestral spirits) related to illness, accidents, and household disputes found in the greetings of baba, baba ria, dodo, happy memes, oa, ete, topora, memes ma awa, dunu, tunu, awa ma awa, and awa ma baba.